Fusobacterium nucleatum in Colorectal Cancer: Ally Mechanism and Targeted Therapy Strategies - Junna Lu; Wei Wei; Diwei Zheng (Research)
Fusobacterium nucleatum (Fn), an oral anaerobic commensal, has recently been identified as a crucial oncogenic contributor to colorectal cancer pathogenesis through its ectopic colonization in the gastrointestinal tract. Accumulating evidence reveals its multifaceted involvement in colorectal cancer initiation, progression, metastasis, and therapeutic resistance to conventional treatments, including chemotherapy, radiotherapy, and immunotherapy. This perspective highlights recent advances in anti-Fn strategies, including small-molecule inhibitors, nanomedicines, and biopharmaceuticals, while critically analyzing the translational barriers in developing targeted antimicrobial interventions. We further propose potential strategies to overcome current challenges in Fn modulation, aiming to pave the way for more effective therapeutic interventions and better clinical outcomes.